As given by the question
There are given that the vertices and focii point is:
![\begin{gathered} \text{vertices: (}\pm6,\text{ 0)} \\ Foci\colon\text{ (}\pm\text{8, 0)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o9fgxz12m88e1beafx609n4hplck4h3457.png)
Now,
From the general form of the equation of hyperbola:
![((x-h)^2)/(a^2)+((y-k)^2)/(b^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/l0626bn68eeug6hf6kdo2ks0r7t63wrkx6.png)
Then,
Firs find the center (h, k) of the hyperbola:
So
We know that the center of hyperbola must be at the midpoint of the given foci:
Then,
The point of foci is:
![(8,\text{ 0) and (-8, 0)}](https://img.qammunity.org/2023/formulas/mathematics/college/vtngetty7xilddubibxdcuxclggxrch4w8.png)
So,
The center of the hyperbola is:
![\begin{gathered} (h,\text{ k)=(}(8+(-8))/(2),\text{ }(0+0)/(2)) \\ (h,\text{ k)=(}(8-8)/(2),\text{ }(0+0)/(2)) \\ (h,\text{ k)=(0, 0)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1t2261fdk3szm4oj532ftxu7m5jdlem683.png)
Now,
Find a which equals half the length of the vertical major axis.
The distance of any focus of the hyperbola from the center is denoted c
So,
The distance of focus (8, 0) and the center (0,0) is:
![\begin{gathered} c=\sqrt[]{(0-8)^2+(0-0)^2} \\ c=\sqrt[]{(8)^2+(0)^2} \\ c=\sqrt[]{64+0} \\ c=\sqrt[]{64} \\ c=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6d4eog3fcumclbrmib50bmfsok81hj2k6d.png)
Now,
The distance of any vertex of the hyperbola from the center is denoted a
So,
The vertex point is:
![(-6,\text{ 0) and (6, 0)}](https://img.qammunity.org/2023/formulas/mathematics/college/n2omsm50n764iyf1e43k65cvgncvc8kuhy.png)
Then,
![\begin{gathered} b=\sqrt[]{(0-6)^2+(0-0)^2} \\ b=\sqrt[]{36} \\ b=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6gyizcpdrwucs9vb2vg9k5npp8t90zufxm.png)
And,
Find a which equals half the length of the horizontal minor axis and we know that the relationship between c, a and b.
So,
From the formula of retaionship between c, a and b.
![\begin{gathered} c^2=a^2+b^2 \\ 8^2=a^2+6^2 \\ 64=a^2+36 \\ a^2=64-36 \\ a^2=28 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/51i3xhdc4lv4d3agc72x9bi8zfcbnyoseu.png)
Then,
From the standard form of the hyperbola:
![\begin{gathered} ((x-h)^2)/(a^2)+((y-k)^2)/(b^2)=1 \\ \frac{(x-0)^2}{28^{}}+\frac{(y-0)^2}{36^{}}=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/47lpgllx61fosca1boua72dy0oh79t2txb.png)
Hence, the standard form of the hyperbola is shown below:
![\frac{(x-0)^2}{28^{}}+\frac{(y-0)^2}{36^{}}=1](https://img.qammunity.org/2023/formulas/mathematics/college/3z1eh2dq5pmm4pop66rjajn8j2ekumuwyw.png)